Delineating investment opportunities for stakeholders in sorghum seed systems: a logit model perspective - Ndossi, Judith; Akpo, Essegbemon; Ojiewo, Christopher Ochieng; Ringo, Justin; Kongola, Eliud; Vernooy, Ronnie; Muricho, Geoffrey; Lukurugu, Gerald Alex; Makoye, Lameck Nyaligwa; Tabo, Ramadjita; Varshney, Rajeev K. (Springer, 2021)
Seed systems are considered as a vehicle through which the sustainable agricultural intensification can be achieved. However, most sub-Saharan African countries have been ineffective to provide sufficient incentives for stakeholders to consistently invest in the seed systems specifically for crops like sorghum. This study was therefore conducted to uncover investment opportunities for stakeholders in the sorghum seed systems to attain an impact-oriented seed production and delivery systems.